Business Process Improvement of Fixed Wing UAV Assembly Process: Imperia Dirgantara Case - Ajibaskoro, Akbar; Wasesa, Meditya (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. Imperia Dirgantara is a company engaged in providing aerial survey solutions using their own university-based research Unmanned Aerial Vehicle (UAV) technology and data processing systems. To anticipate an increasing demand of the aerial survey, the UAV has to be prepared in a short preparation time. Currently, Imperia Dirgantara is facing an issue of lengthy assembly process of the UAV which may lead to lost sales opportunity. In response, this research focuses on providing proposition improvements for the UAV assembly business process, All of data source directly from Imperia Dirgantara internal archives. This business process improvement research is initiated with thorough analysis of bottleneck process in the existing UAV assembly process. Following the bottleneck process identification, we conduct root cause analyses and propose the corresponding business process improvement propositions. Finally we assess the impact of the solution propositions, define the required resources and provide a plan to implement the solution proposition. This research resulting time reduce in processing time as much 12.66% or equal to 10 days. The suggestion of keep improving the current business process instead picking up another option is stated in this research’s report.Keywords: Business Process Improvement; Business Process Model; Bottleneck Analysis; Unmanned Aerial Vehicle; UAV Assembly Process.